2015
DOI: 10.1073/pnas.1504557112
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 critically influences cardiac function via superoxide-MMP9 cascade

Abstract: We have generated low-expressing and high-expressing endothelin-1 genes (L and H) and have bred mice with four levels of expression: L/L, ∼20%; L/+, ∼65%; +/+ (wild type), 100%; and H/+, ∼350%. The hypomorphic L allele can be spatiotemporally switched to the hypermorphic H allele by Cre-loxP recombination. Young adult L/L and L/+ mice have dilated cardiomyopathy, hypertension, and increased plasma volumes, together with increased ventricular superoxide levels, increased matrix metalloproteinase 9 (Mmp9) expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 32 publications
6
28
0
Order By: Relevance
“…This fits very well with the observation that a decreased tissue concentration or a heterozygous knockout of the ET-1 gene is associated with an elevation of blood pressure [24]. Despite lower blood pressure, the heart/body weight ratio in older ET-1+/+ mice is clearly increased as compared to control littermates of the same age.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This fits very well with the observation that a decreased tissue concentration or a heterozygous knockout of the ET-1 gene is associated with an elevation of blood pressure [24]. Despite lower blood pressure, the heart/body weight ratio in older ET-1+/+ mice is clearly increased as compared to control littermates of the same age.…”
Section: Resultssupporting
confidence: 89%
“…This fits well with the observation that a global heterozygous ET-1 knockout in mice causes hypertension (the complete knockout in homozygous ET-1 knockout mice is lethal due to craniofacial malformations [23]). This landmark study was recently confirmed by another independent study showing that a decrease in systemic ET-1 level of up to 35 % of that in the control mice causes hypertension [24]. Notably, in this model blood pressure could be normalized by epithelial sodium channel blockers, indicating that renal tubular sodium transport plays a key role in the pathogenesis of hypertension in these settings.…”
Section: Blood Pressuresupporting
confidence: 64%
“…This fits well with the observation that a global heterozygous ET-1 knockout in mice causes hypertension (the complete knockout in homozygous ET-1 knockout mice is lethal due to craniofacial malformations [23]). This landmark study was recently confirmed by another independent group showing that a decrease in systemic ET-1 level of up to 35 % of that in the control mice causes hypertension [33]. Notably, in this model blood pressure could be normalized by epithelial sodium channel blockers, indicating that renal tubular sodium transport plays a key role in the pathogenesis of hypertension in these settings.…”
Section: Discussionsupporting
confidence: 59%
“…Despite mounting evidence for a causal role of autophagy suppression in the promotion of compensatory hypertrophy (4,11,31,(42)(43)(44)(45)(46), the mechanistic links between pressure overload and adrenergic signaling-induced autophagic suppression have remained largely unsolved. A prior report indicated that endothelin-1 can suppress autophagy by inducing ubiquitination and degradation of Atg14L through ZBTB16-Cullin3-Rock1 E3 ubiquitin ligase complex (47).…”
Section: Discussionmentioning
confidence: 99%